Analisis Pemeliharaan Barang Milik Negara pada Rumah Dinas Kantor Wilayah DJPb Provinsi Jawa Barat Tahun 2021-2023 - Anggun Fakhirah; Dian Fordian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The maintenance of State-Owned Assets (BMN) is a crucial aspect of asset management to ensure sustainability and preserve government investment value. One of the assets requiring special attention is official residences designated for government employees. This study aims to analyze the maintenance of official residences at the Regional Office of the Directorate General of Treasury (DJPb) in West Java Province from 2021 to 2023. Using a qualitative descriptive and comparative approach, data were collected through interviews with key stakeholders, direct observations, and documentation analysis. Findings indicate that out of 84 available housing units, only 14 are in good condition, while the rest suffer from minor to severe damage. The primary challenges in maintenance include budget constraints, delays in central government approvals, and minimal resident involvement in routine upkeep. Although monitoring systems such as the State House Ledger Card (KLRN) and the State Asset Management Information System (SIMAN) have been implemented, their effectiveness requires improvement. This study recommends strengthening coordination among stakeholders, optimizing budget allocation, and utilizing digital technology in asset management to enhance efficiency and effectiveness in maintaining government-owned residences within DJPb